The Role of Al-Quran Hadith Teachers in Increasing Qur’an Reading Interest During the Digital Age - Afriani, Rahmi; Husarida, Husarida; Habibi, Muhammad Fadli; Thontawi, M.; Wiratama, Arif; Firdaus, Heroza (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2023)
In general, the purpose of this study was to analyze the role of Al-Quran Hadith teachers in increasing interest in reading the Al-Quran in the digital era at Madrasah Aliyah Negeri 1 Sarolangun. Specifically, this study aims to find out about: 1) To find out the role of Al-Quran Hadith teachers in increasing interest in reading the Al-Quran 2) To find out the success of Al-Quran Hadith teachers in increasing interest in reading in reading the Qur’an. The type of research used is descriptive qualitative. The data sources of this research are primary data and secondary data. Primary data are the Head of Madrasah Aliyah Negeri 1 Sarolangun, Al-Quran Hadith teachers and also class XI students. As for secondary data from this observation, books, articles, and reference searches that are relevant to research. The data collection method used is observation, interviews, and documentation. Data processing and analysis techniques were carried out through four stages, namely data collection, data reduction, data presentation and drawing conclusions. The results showed that the role of the Al-Quran Hadith teacher in increasing students' interest in reading the Al-Quran in class XI Madrasah Aliyah Negeri 1 Sarolangun namely: The role of the Al-Quran Hadith teacher as educator, mentor, facilitator, motivator, and evaluator.